2014
DOI: 10.3390/resources3010319
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Material Flows and their Socio-Economic and Environmental Implications: A MFA Study on All Countries World-Wide from 1980 to 2009

Abstract: This paper assesses worldwide patterns of material extraction, trade, consumption and productivity based on a new data set for economy-wide material flows, covering used materials for all countries worldwide between 1980 and 2009. We show that global material extraction has grown by more than 90% over the past 30 years and is reaching almost 70 billion tonnes today. Also, trade volumes in physical terms have increased by a factor of 2.5 over the past 30 years, and in 2009, 9.3 billion tonnes of raw materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 26 publications
3
80
0
10
Order By: Relevance
“…Today, global human economic activities require more natural resources than ever before: globalization connects distant regions of the world through trade flows, and emerging economies claim their part of the natural resource pie in order to support their economic growth (UNEP, 2011;Wiedmann et al, 2015). International competition for the control of more or less scarce natural resources use has sharply increased (Schaffartzik et al, 2014, Giljum et al, 2014b. The ongoing combination of resource depletion and increased international competition brings distributional issues of natural resources to the top of the agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Today, global human economic activities require more natural resources than ever before: globalization connects distant regions of the world through trade flows, and emerging economies claim their part of the natural resource pie in order to support their economic growth (UNEP, 2011;Wiedmann et al, 2015). International competition for the control of more or less scarce natural resources use has sharply increased (Schaffartzik et al, 2014, Giljum et al, 2014b. The ongoing combination of resource depletion and increased international competition brings distributional issues of natural resources to the top of the agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Most developed countries have achieved relative material decoupling (lower DMC/ GDP ) over the last 30 years (Giljum et al 2014 ). Müller et al ( 2006 ) and Wiedmann et al ( 2013 ) have both suggested that industrialised nations have lower DMC because they have already established their major infrastructure and their population has grown more slowly than developing countries or has even saturated.…”
Section: The Socio-economic Metabolism Framework and Wealthmentioning
confidence: 99%
“…als Lebensmittel, Futtermittel, Herstellung von Industriegüter oder Treibstoff eingesetzt werden können (Borras und Franco, 2012 (Gellert, 2008). Diese Entwicklung wird durch eine zunehmende Nachfrage nach Ressourcen, sowohl im globalen Norden als auch in den aufstrebenden Schwellenländern (Brand und Wissen, 2012;Giljum et al, 2014;Schaffartzik et al, 2014), und der Finanzialisierung der Natur (White et al, 2012) gefördert. Der Ausbau der Plantagenflächen ist in mehrfacher Hinsicht umkämpft und muss immer wieder mit Hilfe staatlicher Regierungsstellen abgesichert werden.…”
Section: Räumliche Dimensionen Der Naturbeherrschungunclassified